2002
DOI: 10.1073/pnas.052125199
|View full text |Cite
|
Sign up to set email alerts
|

A single domestication for maize shown by multilocus microsatellite genotyping

Abstract: There exists extraordinary morphological and genetic diversity among the maize landraces that have been developed by preColumbian cultivators. To explain this high level of diversity in maize, several authors have proposed that maize landraces were the products of multiple independent domestications from their wild relative (teosinte). We present phylogenetic analyses based on 264 individual plants, each genotyped at 99 microsatellites, that challenge the multiple-origins hypothesis. Instead, our results indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

37
969
11
48

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,225 publications
(1,065 citation statements)
references
References 21 publications
37
969
11
48
Order By: Relevance
“…Molecular data indicate that Mexican maize diverged from Mexican annual teosinte (Z. mays ssp. parviglumis) between 5,689 and 10,093 BP (Matsuoka et al, 2002), which is consistent with the date of the oldest fossil maize of 6,250 BP (Piperno and Flannery, 2001). The early diversification probably occurred in the highlands between the present-day states of Oaxaca and Jalisco, before maize spread into the lowlands (Matsuoka et al, 2002).…”
Section: Maize Diversitysupporting
confidence: 84%
See 1 more Smart Citation
“…Molecular data indicate that Mexican maize diverged from Mexican annual teosinte (Z. mays ssp. parviglumis) between 5,689 and 10,093 BP (Matsuoka et al, 2002), which is consistent with the date of the oldest fossil maize of 6,250 BP (Piperno and Flannery, 2001). The early diversification probably occurred in the highlands between the present-day states of Oaxaca and Jalisco, before maize spread into the lowlands (Matsuoka et al, 2002).…”
Section: Maize Diversitysupporting
confidence: 84%
“…In a recent analysis using molecular markers, Matsuoka et al, (2002) found that races of maize are differentiated at the continental level according to an isolation-bydistance scheme, in which the races that are the farthest apart geographically are also the most genetically distinct. At the country level (in Mexico, for example), the genetic relationships between races of maize are not very clear or well defined, possibly because ''most of the isozyme (and this can be true for other markers) variation in the races of maize in Mexico occurs within, rather than between races'' (Sanchez et al, 2000: 57).…”
Section: Maize Diversitymentioning
confidence: 99%
“…Genome-wide based evidence resoundingly supported the notion on single origins for many crops (e.g. Heun et al, 1997, Badr et al, 2000, Matsuoka et al, 2002 by producing phenograms in which domesticated crops were monophyletic. This data was sometimes in conflict with single gene evidence, such as in the case of barley, which became awkward anomalies to what was largely taken as genetic support for the rapid transition paradigm, and a picture of explosive expansion of agriculturalists out of the centres of origin.…”
Section: Genetic Analysis Within the Rapid Transition Paradigmmentioning
confidence: 98%
“…Spodoptera frugiperda itself also shows evidence for host race formation, specializing on either maize or rice races in the USA (Nagoshi & Meagher 2008). Maize is a crop on which S. frugiperda and its parasitoids have co-occurred for several thousand years in Mexico (Matsuoka et al 2002), thus representing one of the longest associations between a crop plant and associated insects. Sorghum was introduced during the mid-1800s (Smith & Frederiksen 2000), giving ample time for the insects to adapt and specialize.…”
Section: Introductionmentioning
confidence: 99%